Eksistensi Peradaban Islam pada Masa Dinasti Ilkhan Pasca Invasi Mongol - Niswah Qonitah (IAIN Palangka Raya, 2020)
This study was aimed at describing to the assimilation of Islamic culture with Mongols at early of the Hulagu Khan reign and the Islamic civilization atmoshpere during Ilkhan Dynasty under the Mongol Muslim rulers. This study applied historical research method using library approach. The study applied four stages of historical research namely data collection, verification, interpretation, and historical writing. The analysis confirmed that, tirst, the Mongol invasion of the Abbasid dynasty did not cause Muslims lose their Islamic identity. On the contrary, Islamic civilization, then, influenced the life of Mongols at that time. At the same time, although the territory was controlled by Mongols, Muslims contributed a very important role in government from early period of power until the end of Ilkhan Dynasty. Second, the freedom to embrace religion and the authority given by Mongol to Muslims in ruling the government enabled for Muslim to spread out Islamization during Ilkhan Dynasty. This Islamization was further strengthened by the kings of Ilkhan dynasty who later converted to Islam. In the next period, Islam gradually became a part of the government and Islam was acknowledged as the official stateKeyword : Mongols, Islamic Civilization, Ilkhan Dynasty